2016
DOI: 10.1007/s10661-016-5160-3
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation kinetics and risk assessment of thiamethoxam and dimethoate in mango

Abstract: Thiamethoxam and dimethoate are two insecticides used to control hoppers and inflorescence midges in mango. Thiamethoxam (0.008 and 0.016%) and dimethoate (0.06 and 0.12%) were sprayed on Dashehari mango trees during the pre-mature stage of fruit (first week of May) to study their dissipation kinetics and risk assessment in mango fruit. Thiamethoxam dissipated in fruit from 1.93 and 3.71 mg kg(-1) after 2 h of spraying to 0.08 and 0.13 mg kg(-1) after 20 days of spraying at single and double doses, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…After 20 days, residues declined to 80 and 130 ppb for the single and double applications, and no residues were detected after 40 days. This suggests that preharvest withholding periods of 7 to 11 days do comply with the maximum residue limit (500 ppb) for this produce (Bhattacherjee and Dikshit 2016). Balfour et al (2016) measured residues of thiamethoxam and its main metabolite clothianidin in oilseed rape and maize grown from treated seeds.…”
Section: Plants and Apicultural Producementioning
confidence: 87%
“…After 20 days, residues declined to 80 and 130 ppb for the single and double applications, and no residues were detected after 40 days. This suggests that preharvest withholding periods of 7 to 11 days do comply with the maximum residue limit (500 ppb) for this produce (Bhattacherjee and Dikshit 2016). Balfour et al (2016) measured residues of thiamethoxam and its main metabolite clothianidin in oilseed rape and maize grown from treated seeds.…”
Section: Plants and Apicultural Producementioning
confidence: 87%
“…Previous studies found that the half-life of dimethoate in the open field is 2.5 days (Guo et al, 2017), indicating that the residual level of dimethoate is not significantly different in the greenhouse and in the field. The half-life of dimethoate in mango is 2 days (Bhattacherjee & Dikshit, 2016), and the half-life in cucumber is 5.2 days (Geng et al, 2018), indicating that the dissipation of dimethoate is related to the matrix on which it is applied. The half-life of dimethoate in celery grown in Guizhou is 5.4 days, and the half-life of celery in Anhui is 3.5 days (Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The half-life of dimethoate in our study (3.30 days) was lower than that reported for chilly (4.7 days) and okra (5.21 days) (Waghulde et al, 2011). The PHI of dimethoate in parsley (132 days) was higher than that in papaya (3-5 days), guava (3 days), and mango (6-7 days), while it was lower than that in chili (13.63 days) and pomegranate (31.5 days at the standard dose of application and 43.0 days at a double dose of application) (Ahuja et al, 2005;Bhattacherjee and Dikshit, 2016;Khan et al, 2009;Utture et al, 2012;Varghese et al, 2011).…”
Section: The Dissipation Of Chlorpyrifos-methyl Dimethoate Permethrin Iprodione Metalaxyl and Propargite In Parsleymentioning
confidence: 99%